A modern view on the use of information technologies in the process of physical education of student youth - Kashuba, Vitaliy; Asaulyuk, Inna; Diachenko, Anna (Journal of Education, Health and Sport, 2017)
Vitaliy Kashuba, Inna Asaulyuk, Anna Dyachenko Modern view on the use of information technologies in the process of physical education of student youth. National University of Physical Education and Sports of Ukraine, Kyiv; Vinnytsia Mykhailo Kotsiubynskyi State Pedagogical University, Vinnytsia. Topicality The determination of the effectiveness of information technologies for the formation of the informational educational environment of students’ physical education in the system of education and beyond, the identification of the general theoretical basis of learning, for the didactic development of approaches to the introduction of information technologies into the field of physical education of students is the subject of a separate study. Research Objectives To systematize the results of practical experience in the use of information technologies in the practice of physical education of students and determine the ways of the introduction of these technologies in the educational process of students of the speciality "Music". Research Results Considering the tendencies of the development of modern society, its strong informatization, which is connected with the necessity of an increasing involvement of information technologies in the field of education, the authors of the study proposed a series of information technologies of educational and controlling formats. Among the advantages of using information technologies is that the use of information models contributes to the formation of cognitive independence of students while clearly structured main and secondary educational material provides specificity, generalization, and extension of knowledge. Conclusions The analysis of the literature and the data of the ascertaining experiment have become a prerequisite for the development of an information and methodological project "Symphony of Health", which will be divided into the sections "Theoretical Information", "Practical Recommendations", "Homework" and create the preconditions for strengthening the theoretical preparedness of students and increasing the efficiency of the process of physical education. Prospects for further research will be related to the implementation of the informational and methodological project "Symphony of Health" in the process of physical education of students of the speciality "Music".